Pengaruh Kepatuhan Wajib Pajak, Pemeriksaan Pajak, Penagihan Pajak dan Jumlah Wajib Pajak Efektif Terhadap Penerimaan Pajak Penghasilan Wajib Pajak Badan (Studi Kasus pada KPP Pratama Samarinda) - RISKA DEWI ANJAR SARI; Cornelius Rante Langi; Agus Iwan Kesuma (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2020)
This research aims toexamine the effect of Tax compliance, tax audit, tax collection and the number of effective taxpayers in corporate income tax revenue in the Tax Office (KPP) Primary Samarinda. The population used in this research are effectivetaxpayers registered in Samarinda years 2012-2017. There are 72 samples obtained based on saturated sampling method that come from January 2012 to December 2017. Source of data used are secondary data and data analysis technique used is multiple linear regression analysis. Theanalysisshows that the taxpayer compliance variable has a significant effect on income tax revenue at KPP Pratama Samarinda. Meanwhile the variable tax audit, tax collection and the number of effective taxpayers have no significant effect on corporate income tax revenue at KPP Pratama Samarinda.